A molecular phylogeny of Zygopterans (Insecta, Odonata) of Kerala, India - C. Nitha Bose; Anu Boswell; Francy K. Kakkassery (Journal of Insect Biodiversity and Systematics)
Molecular phylogenetic reconstruction of the suborder Zygoptera based on sequences of the nuclear ribosomal gene 18S and mitochondrial gene COI was carried out using species collected from India. Sequence samples of 19 species belonging to 7 families of Zygoptera were used for the analysis. All the existing family levels in Zygoptera were confirmed as monophyletic clades in both analyses. While the 18S analysis resolved deep relations well, the COI analyses supported recently diverged clades. The analysis based on the COI gene showed the monophyly of families Coenagrionidae, Calopterygidae, Lestidae, Chlorocyphidae, and Platycnemididae and was found as a distinct clade. The remaining families Platystictidae and Euphaeidae were polyphyletic to the former clade showing more genetic divergence. In the 18S analysis, from the common ancestor, a monophyletic clade of Coenagrionidae, Platycnemididae, Lestidae and Chlorocyphidae evolved. Euphaeidae, Platystictidae and Calopterygidae were polyphyletic.